The Effect of Product Quality, Distribution Channels and Service Quality on Customer Satisfaction Spotlights - Rosinta Romauli Situmeang; Wandy Tanzil; Vincent Tandratama; Suryo Anwar Putra (Institute of Computer Science (IOCS), 2020)
The purpose of this research is to examine the effect of Product Quality on the Customer Satisfaction of Spotlights of PT XYX. The research method used is linear regression analysis. The population in this study was 191 customers and the sample was 131 luxent spotlight customers. The results of simultaneous and partial calculations of Product Quality, Distribution Channels and Service Quality affect the Customer Satisfaction Spotlights of PT XYX.